(untitled) (Research, Society and Development, 2021)
This article aims to analyze the structural process as a way of protecting fundamental rights, in particular, environmental law. First, an identification of the appearance of this category of litigation is presented to identify its relevance. In this context, the definition of structural litigation is presented, with the possibility of structural decisions emanating from the Judiciary, differentiating from public interest litigation and collective actions, to demonstrate that it is a more complex demand, aimed at correcting or prevention of the problem in a systemic way. The research is of theoretical-bibliographic and documentary nature, following the descriptive-analytical method that instructed the analysis of constitutional, infraconstitutional and jurisprudential legislation, as well as the use of doctrine. It concludes by the need to use structural processes for the realization of fundamental rights, either in preventive or reparative form, as it brings a solution that goes far beyond the problem that initially caused the need to resort to the Judiciary.